Investigation of algorithms for prevention of congestion in computer networks at level of TCP protocol using Mininet network emulator (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2021)
This article examines the performance and values of network parameters when applying different algorithms to control network congestion. The Mininet network emulator is used, which creates software-defined networks that give us the opportunity to conduct various experiments with the network and manipulate its parameters. The conclusion is made for the best algorithm to prevent network congestion. An estimate of the relative value of the error was made, which shows that in Mininet deviations in the values can be observed with a larger number of hosts in the network.